Angiotensin receptor/Neprilysin inhibitor effects in CRTd non-responders: From epigenetic to clinical beside. (August 2022) - Sardu, Celestino; Massetti, Massimo; Scisciola, Lucia; Trotta, Maria Consiglia; Santamaria, Matteo; Volpicelli, Mario; Ducceschi, Valentino; Signoriello, Giuseppe; D'Onofrio, Nunzia; Marfella, Ludovica; Casolaro, Flavia; Amico, Michele D.'; et al.
Abstract: Objectives: We evaluated whether Angiotensin receptor/Neprilysin inhibitors (ARNI) reduce heart failure (HF) hospitalizations and deaths in cardiac resynchronization therapy with defibrillator (CRTd) non-responders patients at 12 months of follow-up, modulating microRNAs (miRs) implied in adverse cardiac remodeling. Background: adverse cardiac remodeling characterized by left ventricle ejection fraction (LVEF) reduction, left ventricular end-systolic volume (LVESv) increase, and the 6-minute walking test (6MWT) reduction are relevant pathological mechanisms in CRTd non-responders and could be linked to changes in miRNAs (miRs), regulating cardiac fibrosis, apoptosis, and hypertrophy. Methods: miRs levels and clinical outcomes (LVEF, cardiac deaths, and 6MWT) were evaluated at baseline and one year of follow-up in CRTd non-responders divided into ARNI-users and Non-ARNI users. Results: At baseline, there were no differences in levels of inflammatory markers, miR-18, miR-145, and miR-181 (p > 0.05) between Non-ARNI users (n 106) and ARNI-users (n 312). At one year of follow-up, ARNI-users vs. Non-ARNI users showed lowest inflammatory markers (p < 0.01) and miR-181 levels (p < 0.01) and higher values of miR-18 (p < 0.01)and miR-145 (p < 0.01). At one year of follow-up, ARNI-users had a higher increase of LVEF (p < 0.01) and 6MWT (p < 0.01) along with a more significant reduction of LVESv (p < 0.01) compared to Non-ARNI users. Cox regression analysis evidenced that ARNI-based therapies increase the probability of anti-remodeling effects of CRTd. Based on symptomatic improvements, echocardiographic and functional classification improvements, 37 (34.9%) patients among ARNI-users became responders, while only twenty (6.4%) patients became responders among Non-ARNi-users. Conclusions: ARNI might influence epigenetic mechanisms modulating miRs implicated in the adverse cardiac remodeling responses to CRTd. Graphical Abstract: ga1 Highlights: Angiotensin receptor/Neprilysin inhibitors (ARNI) could reduce heart failure (HF) hospitalizations and deaths in cardiac resynchronization therapy with defibrillator (CRTd) non-responders' patients. ARNI could modulate the microRNAs (miRs) implied in cardiac remodeling. At one year of follow-up, the ARNI increased the LVEF and 6MWT, and reduced LVESv. ARNI lead to anti-remodeling effects in CRTd non-responders via miRs modulation.